The Surgical Treatment of Bilateral Benign Nodular Goiter: Balancing Invasiveness With Complications - Rayes, Nada (Deutscher Arzte Verlag, 2014)
BACKGROUND: About 100 000 thyroid operations are performed in Germany each year. There is a current trend toward more radical surgery for bilateral euthyroid nodular goiter. In recent years, thyroid specialists and specialty guidelines have recommended total thyroidectomy, because it ensures that nodules will not recur and already provides an adequately radical excision in case an incidental carcinoma is found postoperatively on histological study of the specimen. An alternative method is unilateral hemithyroidectomy with contralateral subtotal resection (the Dunhill procedure). METHODS: Selective literature review. RESULTS: Three randomized controlled trials (RCTs) have compared the long-term outcomes of different surgical methods. In addition, retrospective studies have been published, but their findings must be interpreted with caution because of limitations of method. When all of the data are considered, it appears that radical procedures are often not justified. According to the RCTs, nodules arose during long-term follow-up in 4.7–14% of patients who had undergone subtotal resection; yet, in the two more recent and methodologically more valid RCTs, surgery for recurrent goiter was needed in only 0–0.5% of patients treated with a Dunhill procedure and given adequate hormone supplementation. Most incidental carcinomas are papillary microcarcinomas; this entity is usually adequately treated with hemithyroidectomy. The reported complication rates of total thyroidectomy for permanent hypoparathyroidism in particular range from 0.5% (in specialized centers) to 10% (in a cross-sectional study) and thus seem higher than the corresponding rate for a Dunhill procedure (1–2%). CONCLUSION: Total thyroidectomy has significant risks and should only be performed if the indication has been critically assessed. Alternative methods such as the Dunhill procedure are often radical enough with a much lower rate of postoperative hypoparathyroidism; they remain an important option in thyroid surgery. Further RCTs with sufficient long-term follow-up are needed so that the different surgical methods can be reliably compared in detail.